HOW COOPERATIVE SOCIETIES ENHANCE GENERAL WELLBEING THROUGH HOUSING PROVISION AND SERVICES IN NIGERIA - Lawal, Musediq Olufemi (Annals of Spiru Haret University. Economic Series, 2021)
This study discusses the activities of cooperative societies in meeting the challenges of housing provision in the face of seeking and repayment processes. The cooperative societies in formal and informal settings were studied. Cooperative societies in 2 tertiary institutions in Nigeria were used as cases for formal setting. Informal setting was represented by the oldest Coordinating Cooperative Union in Ibadan, Nigeria. A total of 330 respondents took part in the study. Questionnaire and interviews were utilized to collect data for the study. The findings revealed that all the cooperative societies ran multipurpose services with housing loan services being equally included. These services included mass purchasing of land (b) acquisition of rapid urbanization. The study made an exposition of housing and related services, loan fixed assets (c) housing loans to members who are about to complete their personal houses or in the process of having one. Cooperative societies were seen as the easiest channels of securing access to affordable housing due to absence of bureaucratic bottleneck and insurmountable conditions. The general feeling was that decision making on how, when and to whom the loan should be given was faster, reliable and enhancing social, mental and physical stability for better productivity.